PERAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY ATAS KINERJA KEUANGAN PERUSAHAAN (Media Riset Akuntansi, 2022)
This study aimed to examine the effect of Corporate Social Responsibility disclosure to financial performance of mining companies listed in Indonesia Stock Exchange from 2011-2015, whereas the company's financial performance is measured by Return On Assets, Return on Equity, Operating Profit Margin, and Net Profit Margin. The population of this study is all mining companies listed in Indonesia Stock Exchange from 2011-2015. The sample used in this study is 37 samples as a result of elimination by using purposive sampling, in which 3 removed samples are outliers. The method used in analyzing data is multiple regression analysis. Corporate Social Responsibility disclosure is measured by CSR Rating System of Global Reporting Initiative Index 2002, modified by Sutantoputra (2008). This study concludes that Corporate Social Responsibility affects only the Operating Profit Margin. Meanwhile, Corporate Social Responsibility does not affect Return On Assets, Return On Equity, and Net Profit Margin. The results of this study suggested that 2015 was the worst year for the mining sector in Indonesia. This is caused by the decrease of commodity prices in the mining sector and also the high level of debt incurred by mining companies. This is the reason why mining companies in Indonesia do not earn optimum operating income and/or net income, thus those companies do not maximize the disclosure of CSR in presenting annual report.